ChemInform Abstract: Influence of an Internal Trifluoromethyl Group on the Rhodium(II)‐Catalyzed Reactions of Vinyldiazocarbonyl Compounds. Issue 35 (8th August 2013) - Nikolaev, Valerij A.; Supurgibekov, Murat B.; Davies, Huw M. L.; Sieler, Joachim; Zakharova, Valerija M.
Abstract Incorporation of a trifluoromethyl group into the starting compounds strongly reduces the tendency of intermediate vinyloxocarbenoids to undergo intermolecular reactions.